Dialect variation and social identity - Alfiyatus Sa'adah; Shinta Nur Kumala; Sony Sukmawan; Roosi Rusmawati (Pioneer: Journal of Language and Literature, 2025)
This study examines how dialect variation among Javanese speakers in a multicultural community functions as a resource for identity negotiation, social positioning, and group solidarity. Grounded in sociolinguistic and sociocultural perspectives, it investigates how speakers shift between ngoko, madya, and krama in everyday interaction. Using a qualitative case study design involving three participants (n = 3), data were collected through semi-structured interviews and participatory observation. The findings indicate that dialect choice reflects age, social status, and relational proximity, and operates as a symbolic marker of belonging and identity performance. Participants also demonstrate metapragmatic awareness in adapting their speech in intercultural encounters. However, a generational decline in the use of krama reveals tensions between language maintenance and sociocultural change. This study highlights the practical importance of dialect awareness for fostering mutual understanding in multicultural settings and contributes to the discussion of intra-language translingualism, understood as strategic shifting across varieties within a single language to negotiate social meaning and identity.